Splenic abscess due to Salmonella enteritidis - Hatice Çabadak; Ayşe Erbay; Kerem Karaman; Süha Şen; Yasemin Tezer Tekçe (MDPI AG, 2012)
Splenic abscess is a very rare complication of non-typhoidal Salmonella infections. We report a case of splenic abscess caused by Salmonella enteritidis. The patient is a 63-year-old woman with diabetes mellitus and underwent splenectomy. This case suggests that the patients with comorbities are at increased risk for invasive infections in non-typhoidal Salmonella infections.